2017
DOI: 10.1039/c6sm02007k
|View full text |Cite
|
Sign up to set email alerts
|

On tuning microgel character and softness of cross-linked polystyrene particles

Abstract: Polystyrene (PS) microgel colloids have often been used successfully to model hard sphere behaviour even though the term "gel" invokes inevitably the notion of a more or less soft, deformable object. Here we systematically study the effect of reducing the cross-link density from 1 : 10 (1 cross-link per 10 monomers) to 1 : 100 on particle interactions and "softness". We report on the synthesis and purification of 1 : 10, 1 : 25, 1 : 50, 1 : 75 and 1 : 100 cross-linked PS particles and their characterization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
4
13
0
Order By: Relevance
“…Thus the motions of the particles at any height, follow a shear deformation, but that a higher shear rate forms close to the lower surface . This suggests that shear banding, generally observed for suspensions with attractive interactions 51 , occurs in our system. These measurements show the ability of our setup to measurement local shear rates, with spatial resolution of ≈ 100 µm.…”
Section: B Dynamic Light Scatteringsupporting
confidence: 65%
See 2 more Smart Citations
“…Thus the motions of the particles at any height, follow a shear deformation, but that a higher shear rate forms close to the lower surface . This suggests that shear banding, generally observed for suspensions with attractive interactions 51 , occurs in our system. These measurements show the ability of our setup to measurement local shear rates, with spatial resolution of ≈ 100 µm.…”
Section: B Dynamic Light Scatteringsupporting
confidence: 65%
“…Here, we consider polystyrene microgel particles suspended in a good solvent, 2-ethyl-naphtalene (2EN), of refractive index n = 1.599. The structure and dynamics of these suspensions at volume fractions corresponding to a glass phase have been studied in detail in the absence of shear 50,51 . Using measurements of the elastic modulus 51,52 , it has been shown that their interaction potential is well described by u(r) ∼ r r 0 n with n as large as 99 51 .…”
Section: A the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Colloidal hydrogels are a common subtype where the continuous phase is water. Often, but not always, these networks exhibit conformational changes in response to changes in their environment, such as the solvent composition or temperature 1 , 4 , 5 . The sensitivity to external stimuli, such as temperature, pH, or solvent conditions, is an essential feature of many microgels, in particular for the most widely studied type of microgels, based on pNIPAM (poly-N-isopropylacrylamide) and its derivatives 1 , 6 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, 3 we have systematically synthesized a large variety of polystyrene micro-gels of different sizes and degrees of cross-linking. For these, we studied the relation of dry particle sizes, swelling ratios in the good solvent 2-ethylnaphthalene, phase boundaries and light scattering properties.…”
mentioning
confidence: 99%